EFFECT OF DENTURE CLEANSERS ON HARDNESS OF ACRYLIC SOFT LINER - Rani Purba (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Plasticizer is the content of the soft liner (with soft acrylic polymer (poly ethylmethacrylate)) or denture tissue conditioner material that maintains the soft said material. However, it will release as a result of the saliva or water solution being absorbed that could be effected on the acrylic soft liner physical properties such as a hardness. Selection of the denture cleanser is very important to minimize its impact, which is the traditional plant cinnamon (Cinnamomum burmani) can be used as an alternative of natural denture cleansure agents besides alkaline peroxide chemicals used frequently. The aim of this study was to determine the effect of different denture cleansers on hardness of acrylic soft liner. Method: Eighteen cylindrical acrylic soft liner samples (15mm x 10 mm (ASTM: D-2240 64T)) were divided into 3 groups : group I aquadest immersion, group II alkaline peroxide immersion and group III cinnamon immersion. The measurement of acrylic soft liner hardness was done using Shore A hardness D2240 after 7 days of immersion. The results were submitted to one-way ANOVA and post hoc Bonferroni. Results: The highest average of acrylic soft liner hardness was shown by alkaline peroxide immersion group followed by cinnamon immersion group and aquadest immersion group sequentially. There was a significant difference between all groups (p<0.05). Conclusion: There was effect of different denture cleansers on hardness of acrylic soft liner. Keywords: soft liner, denture cleanser, cinnamon